Globalisasi Transportasi dalam Membuka Peluang Usaha Keagenan yang Didukung oleh Program Tol Laut di Indonesia - Iswanto Iswanto; Handoyo Widyanto (Sekolah Tinggi Maritim Yogyakarta, 2019)
Port activities with its high economic value will be a strategic target for all stakeholders, between Government as policy regulator trough State-Owned Enterprises which is monopolistic and national private companies which also wants to take benefit from the activities. Commonly monopolistic activity tend to be distorted for example activities of vessel’s arrival, berthing, loading and unloading activities which deal with port regulator/administrator to activities of vessel’s departure Regulation condueted by government using monopolistic way become a problem due to the contribution of private companies as well in the process of ship physical affair, vessel manning loading and unloading which recently left-behind.